Female Bias in Systemic Lupus Erythematosus is Associated with the Differential Expression of X-Linked Toll-Like Receptor 8 - McDonald, Gabrielle; Cabal, Nicholas; Vannier, Augustin; Umiker, Benjamin; Yin, Raymund H.; Orjalo, Arturo V.; Johansson, Hans E.; Han, Jin-Hwan; Imanishi-Kari, Thereza (Frontiers in Immunology, 2015)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by the production of anti-nuclear antibodies. SLE is one of many autoimmune disorders that have a strong gender bias, with 70-90% of SLE patients being female. Several explanations have been postulated to account for the severity of autoimmune diseases in females, including hormonal, microbiota, and gene dosage differences. X-linked TLRs have recently been implicated in disease progression in females. Our previous studies using the 564Igi mouse model of SLE on a Tlr7 and Tlr9 double knockout background showed that the presence of Tlr8 on both X chromosomes was required for the production of IgG autoantibodies, Ifn-I expression and granulopoiesis in females. Here we show the results of our investigation into the role of Tlr8 expression in SLE pathogenesis in 564Igi females. Female mice have an increase in serum pathogenic anti-RNA IgG2a and IgG2b autoantibodies. 564Igi mice have also been shown to have an increase in neutrophils in vivo, which are major contributors to Ifn-α expression. Here we show that neutrophils from C57BL/6 mice express Ifn-α in response to 564 immune complexes and TLR8 activation. Bone marrow-derived macrophages from 564Igi females have a significant increase in Tlr8 expression compared to male-derived cells, and RNA-FISH data suggests that Tlr8 may escape X-inactivation in female-derived macrophages. These results propose a model by which females may be more susceptible to SLE pathogenesis due to inefficient inactivation of Tlr8.